2015
DOI: 10.5624/isd.2015.45.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital periapical radiography and cone-beam computed tomography in detecting external root resorption

Abstract: PurposeThe purpose of this study was to evaluate and compare the efficacy of cone-beam computed tomography (CBCT) and digital intraoral radiography in diagnosing simulated small external root resorption cavities.Materials and MethodsCavities were drilled in 159 roots using a small spherical bur at different root levels and on all surfaces. The teeth were imaged both with intraoral digital radiography using image plates and with CBCT. Two sets of intraoral images were acquired per tooth: orthogonal (PA) which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 11 publications
2
37
0
3
Order By: Relevance
“…After that, the full texts of the reserved 31 citations were obtained and evaluated per the inclusion criteria. Finally, 15 studies were included in the systematic review [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ( Figure 1). Among the enrolled studies, nine studies reported the diagnos- tic efficacy of CBCT with a sample size of 1097 suspected ERR sites, and 11 reported information of PR with a sample size of 1072 sites (five studies focused on both modalities).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…After that, the full texts of the reserved 31 citations were obtained and evaluated per the inclusion criteria. Finally, 15 studies were included in the systematic review [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ( Figure 1). Among the enrolled studies, nine studies reported the diagnos- tic efficacy of CBCT with a sample size of 1097 suspected ERR sites, and 11 reported information of PR with a sample size of 1072 sites (five studies focused on both modalities).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…The accuracy of detection of root resorption has been shown to be superior using CBCT compared with intraoral radiography (27,28). A higher diagnostic accuracy in detecting resorption may, however, not be of clinical interest as the long-term prognosis even for severe root resorption is relatively good (29).…”
Section: Discussionmentioning
confidence: 99%
“…The results of application of two CBCT systems at different voxel resolutions for detecting small cavities of internal resorption were evaluated in a study by Kamburoglu & Kursan, in which the high resolutions of both systems yielded similar results in identifying internal resorption lesions, although one of the two systems somehow produced better results at low resolution [21,22,23].…”
Section: Discussionmentioning
confidence: 99%